RISK FACTORS FOR STUNTING IN CHILDREN AGED 24-59 MONTHS IN TUKKA DOLOK VILLAGE, PAKKAT DISTRICT, HUMBANG HASUNDUTAN REGENCY INDONESIA - Sitorus, Grace Tina Sari; Pane, Masdalina; Asima Sirait; Donal Nababan; Netty Sembiring (Indonesia Epidemiological Journal, 2023)
ABSTRACT Background: Stunting is a form of growth failure (growth faltering) due to the accumulation of insufficient nutrition that lasts for a long time starting from pregnancy until the age of 24 months. The purpose of this research to analyze the risk factors for stunting in children aged 24-59 months in Tukka Dolok Village, Pakkat District, Humbang Hasundutan Regency year 2022. Methods: This type of research observational using a case control study design. The population in this study were all households with children aged 24-59 months, the sample size in this study was calculate dusing random sampling namely as many as 63 children, 21 children as case samples and 42 children as control samples. Data were analyzed using univariate, bivariate and multivariate analysis using chi-square test and logistic regression analysis. Results: The results of the bivariate analysis showed that there was a relationship between mother's knowledge about food intake (p=0.001 <α=0.05), parenting patterns (p=0.007 <α=0.05), environmental health (p=0.001 <α=0.05 ), with the incidence of stunting. The results of multivariate analysis showed that the most dominantly related variable was environmental health (p=0.017; OR=5.075 95% CI 1.344-19.160). Conclusion: the influence of mother's knowledge about food intake and environmental health is very large on the incidence of stunting. So it is recommended to improve sanitation facilities in the household as well as increase the mother's knowledge about food intake until she is able to apply it.